5 - Housing Cape Town’s Forgotten Dead: Conflict in the Post-apartheid Public Sphere: https://doi.org/10.4314/ad.v35i4.70218 - Green, Louise; Murray, Noëleen (Africa Development, 2021)
On 28 May 2008, the Cape Town Partnership Company Executive Officers’s newsletter reported on an ‘Interfaith ceremony at Prestwich Place [sic]’ to ‘consecrate’ a new ossuary building recently completed in Cape Town’s central business district. The announcement placed the Ossuary alongside other Partnership initiates and events such as the Harvest Festival, the Creative Cape Town initiative, and the upgrading of the Cape Town Station and the Grand Parade managed through the Partnership and the City Improvement District. The building of the Ossuary is intended to memorialise and bring closure to the contestations over the re-emergence of burial spaces in the city that have taken place in Cape Town since 2004. Presented as a successful ‘partnership’ between the Prestwich Place Project Committee, the City of Cape Town, the South African Heritage Resources Agency, the District Six Museum and Heritage Western Cape, this symbolic act of closure has been hailed a breakthrough in terms of heritage practice by practitioners and city officials alike. In this paper we visit the space of the Ossuary and its associated exhibition in the city, and reflect on the relationship between life space and burial space in Cape Town. Following the official path of the exhibition we pause to attach our own notes – a series of fragmentary interventions which trouble the smooth surface of containme t. We use the experience of walking to reflect on the architecture of closure.